Nilai-Nilai Multikultural dalam Kebudayaan Pendalungan di Kabupaten Jember - Arrovia, Zahira Irhamni (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2021)
Jember is a district part of the province of East Java, Indonesia. Since the conversion of Jember as an independent agency during the Dutch East Indies government, the city has grown rapidly. Public facilities began to be established and the wave of population migration was increasing. Generally they come from Madura and Java as the majority ethnicity, while the ethnic minorities are Chinese and Arabs. As a result of the meeting of these ethnic groups, especially Madura-Javanese, there was a fusion of their respective cultures, resulting in a new culture called Pendalungan. Administratively, Pendalungan is attached to the Tapal Kuda area, including Jember. In addition, its multi-ethnic population makes Jember a multicultural district. Therefore, in writing this article, it aims to discuss the Pendalungan culture, analyze the Pendalungan culture in Jember, and analyze the multicultural values ​​of the Pendalungan culture in Jember. The method used is descriptive qualitative by utilizing relevant written sources using content analysis data analysis techniques. Based on the analysis obtained by the author, the multicultural values ​​in the Pendalungan culture in Jember include mutual respect, mutual respect, maintaining group solidarity, eliminating bad prejudice, tolerance, and helping each other.